Evidence for indirect strengthening through reactivation of contextually bound memories - Juan Cruz Beron; Luz Bavassi; Maria E. Pedreira; Rodrigo S. Fernández (Communications Psychology)
Abstract Episodic memory is, by definition, associative; retrieving one event often triggers the recollection of another related event. Memory reactivation has been shown to strengthen reactivated memories, but its effects on related, non-reactivated memories remain unclear. This study investigated whether reactivation of a consolidated target memory could indirectly enhance the retention of peripheral information acquired in the same context. We hypothesized that reactivating a consolidated target memory would improve its retention and strengthen contextually associated memories. To test this, we conducted four experiments (n = 238) in which participants first learned face-name pairs (target memory) alongside everyday objects (peripheral memory). On Day 2, a subset of participants underwent a reactivation intervention using incomplete reminders of the target memory, while others received a control intervention. On day 3, memory performance for both the target and peripheral memories was assessed. Results revealed that reactivation significantly improved the retention of target and peripheral memories when acquired in the same context. However, when peripheral memories were learned in a different context, reactivation of the target memory did not produce the same indirect strengthening effect. These findings suggest that the indirect strengthening of consolidated memories through reactivation is context-dependent and may rely on the shared spatiotemporal acquisition context. This study provides new insights into the mechanisms of memory reactivation and its broader impact on related non-reactivated memories.